Thinking through Thinking with. - Levinson, Marjorie (Modern Philology, 2024)
This essay takes up unfinished business from my 2018 book, Thinking through Poetry —namely, how my notion and practice of "thinking with" departs from the norm for surface reading, affect study, reparative reading, and the like. I bring together an unlikely set of writers, chosen for the freshness, precision, and specificity of their inquiries into the process of thinking. The key figures are (in order of citation) Eugene Gendlin, J. H. Prynne, Jonathan Kramnick, W. V. Quine, and Sharon Cameron. Prynne, Kramnick, and Cameron offer insights specific to the practice of literary critical "thinking with."